Evaluation of Flood Risk Reduction Project at Tenggang River, Semarang City, Central Java Province, Indonesia - Nuon Udom (Journal of the Civil Engineering Forum, 2018)
Evaluation of flood risk reduction at Tenggang River is needed to reduce the urban and coastal flood from high-intensity rainfall and sea level rise. This paper mainly discusses rainfall frequency analysis, simulation of hydraulic structure performed by HEC-RAS 5.0.3, and the proposed alternative flood mitigation for 25-year flood return period. Hydrology and hydraulic was analyzed to investigate the flooding risk. The result of simulation illustrated the improvement channel condition by normalization the riverbed and the increase of levee to solve flood inundation at Tenggang River using the designated flood return period (25 years of return period, Q25 = 119 m3/s). The result of simulation showed that the hydrologic-hydraulic modeling is acceptable compared to the report from the office of public work in Semarang City.